2020
DOI: 10.4103/jfmpc.jfmpc_265_20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of retinoblastoma in north India: Implications for primary care and family physicians

Abstract: Background: Retinoblastoma is the most common primary intraocular malignancy among children. Despite being curable in early stages, majority of the cases in India present in late stages, when outcomes are very poor. Objectives: The aim of this study was to assess the epidemiological profile, clinical characteristics, and treatment practices among retinoblastoma patients in north India. Materials and Methods: Data on all patients with retinobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
4
7
0
Order By: Relevance
“…One recent article from India showed that it is ∼35 months [20] though few other Indian articles showed the range is 29-33 months [21,22]. Fifty three percent of our children presented between 13 months to 59 months which is similar to the finding of Nidhi et al [23]. Our sixteen percent patients presented at more than 5 year of age which is 11% by Sing et al in India and 3.5% by Bonanomi et al in Brazil .…”
Section: Discussionsupporting
confidence: 80%
“…One recent article from India showed that it is ∼35 months [20] though few other Indian articles showed the range is 29-33 months [21,22]. Fifty three percent of our children presented between 13 months to 59 months which is similar to the finding of Nidhi et al [23]. Our sixteen percent patients presented at more than 5 year of age which is 11% by Sing et al in India and 3.5% by Bonanomi et al in Brazil .…”
Section: Discussionsupporting
confidence: 80%
“…Although it is curable in the early stages, the majority of the patients in India present in the late stages as seen in our experience. Enucleation was done after chemotherapy treatment in all the cases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the study population was 13 months. As per the study conducted by Shields et al ,[ 5 ] Arora et al, [ 19 ] and Gupta et al, [ 20 ] 90% of cases were diagnosed before 5 years of age. In the current study, female children were found to be affected more as the female: male ratio was 23:19.…”
Section: Discussionmentioning
confidence: 79%
“…This is not in concordance with various studies which reported that retinoblastoma does not have any gender predilection. [ 20 21 ] Maximum patients in the current study had unilateral presentation as 40 patients were found to have tumor in one eye. Bilateral presentation was found in two patients.…”
Section: Discussionmentioning
confidence: 84%